Gender differences in expressing love in marriage: stability across generations and cultures - Huić, Aleksandra (Array, 2012)
Although love has been tied to different behaviors for men and women, it is unclear whether individuals intend to express their love through such behaviors. In order to identify the ways in which men and women report showing love, we developed the 40-item Ways of Showing Love Scale. The specific ways of showing love fell into six broad categories: (1) communal and sacrificial behaviors, (2) physical affection, (3) verbal affection, (4) domestic instrumentality, (5) emotional openness and support, and (6) chivalry. Upon identifying the classes of behavior individuals report using to express love, we examined: (a) gender differences in the ways spouses report showing love ; (b) the stability of these differences across three generations of couples ; and (c) whether feelings of love predicted the ways spouses report showing love. To do so, we gathered data from 302 Croatian and 456 Serbian married couples, who came from a wide range of education and employment backgrounds. In order to test for generational differences, couples were divided into three age brackets (20–35, 36–54, and 55–87 years). Lending support to the validity of our scale, spouses’ feelings of love predicted all six ways of showing love. Both 56 husbands and wives reported expressing love through affection and by respecting each other’s needs. Whereas women indicated they show love by being open and supportive, as well as by doing housework, men indicated they show love through physical affection and acts of chivalry. Results were stable across generations and cultures.